Power to choose? Examining the link between contraceptive use and domestic violence - Manini Ojha; Karan Babbar (Global Labor Organization (GLO), 2023)
Contraception is a crucial tool that empowers women to control their bodily autonomy. Concurrently, violence against women remains a pressing public-health issue depleting women's autonomy. We establish a causal link between the decision to use contraception and the occurrence of intimate partner violence. Utilizing newly available nationally representative data for India, we use an instrumental variable approach to estimate our causal effects. Using exogenous variation in the cluster average of women's exposure to family planning messages via radio, we find that if the decision to use contraceptives is solely taken by the woman, she is at a significantly higher risk of physical, sexual and emotional domestic violence. We estimate bounds of our effects by assuming the IV to be plausibly exogenous where we relax the exogeneity condition. Our findings underscore the importance of reproductive health in initiatives that reduce domestic violence and targeted policies towards men's understanding of family planning.
Keywords: I15; J12; J13; J16; C26; 330; contraception; intimate partner violence; mass-media; family planning; NFHS-5; India